1994
DOI: 10.1159/000227383
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic Primary Malignant Neoplasms Associated with Hepatocellular Carcinoma: High Occurrence of B Cell Tumors

Abstract: In a consecutive series of 317 patients with hepatocellular carcinoma (HCC), 32 (10.1%) had 35 extrahepatic primary malignant neoplasms (PMNs) (3 patients had triple cancers). Twenty-five PMNs occurred before the diagnosis of HCC, 7 were synchronous and 3 metachronous. These 35 PMNs were: 6 cancers of the colon, 3 of the stomach, 1 of the rectum, 4 of the breast, 2 of the lung, 1 of the larynx, 3 of the prostate, 1 of the penis, 1 of the urinary bladder, 1 of the uterus, 2 of the skin, and the remaining 10 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 11 publications
3
26
1
Order By: Relevance
“…Genitourinary (mainly prostate) and colorectal tumors are described as the most prevalent sites in Western series [1, 5, 9, 11, 13, 15]. Previous Japanese studies consistently reported gastric cancer as the most frequent EHPM in HCC patients [2–4, 10, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Genitourinary (mainly prostate) and colorectal tumors are described as the most prevalent sites in Western series [1, 5, 9, 11, 13, 15]. Previous Japanese studies consistently reported gastric cancer as the most frequent EHPM in HCC patients [2–4, 10, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Common oncogenic cellular pathways may contribute to the development of hepatocellular carcinoma and chronic lymphocytic leukaemia. The relationship between non-Hodgkin lymphoma and hepatocellular carcinoma1 2 has been published. However, no conclusions can be drawn from these studies as some of the patients reported had serology consistent with prior viral hepatitis infection, which can be associated with both types of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an Italian study of 317 patients with HCC found B cell-derived neoplasms to represent the most frequent cancers associated with HCC, accounting for 10 of 35 extrahepatic primary neoplasms, or 28.6% [1]. Disagreement between these two reports concerning the frequency of B cell neoplasms in patients with HCC is likely to involve the difference in ethnicity between study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…These were varied: 7 cases of NHL, 2 cases of multiple myeloma, and 1 chronic lymphocytic leukemia [1]. These cases also showed a relatively nonspecific distribution pattern, that of double cancers with the B cell neoplasms involving essentially any part of the body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation